The effects of energy density and heat treatment on the microstructure and mechanical properties of laser additive manufactured Haynes 282. (July 2021) - Boswell, John; Jones, Jonathan; Barnard, Nicholas; Clark, Daniel; Whittaker, Mark; Lancaster, Robert
Graphical abstract: Highlights: Mechanical and microstructural behaviour of LPBF Haynes 282 has been assessed. Solution aging treatment eradicates anisotropic behaviour found in as-built condition. Transition in behaviour corroborated by mechanical and microstructural findings. Abstract: The nickel-based superalloy Haynes 282 is a promising candidate material among the existing batch of aerospace alloys for manufacture via laser powder bed fusion (LPBF). LPBF Haynes 282 has a strong preference for epitaxial grain growth in the (0 0 1) orientation, promoting inhomogeneous grain morphologies and anisotropic mechanical behaviour. In this paper, LPBF Haynes 282 specimens have been extracted from perpendicular and parallel orientations in respect to the primary vertical build direction and studied in their original as-built form and when exposed to a solution and age heat treatment. The effect of alternative energy densities is also considered in the different conditions. Results show that the numerous processing variables discussed in this research have a direct influence on the morphology of the final grain structure. Although a strongly anisotropic microstructure was present in the as-built material in both respective orientations, this behaviour was eradicated following the solution and aging heat treatment through recrystallisation, and the alleviation of local texture and misorientation to help produce a more uniform equiaxed grain morphology. The subsequent mechanical behaviour has been assessed through hardness, tensile and creep stress rupture testing, and results have corroborated the microstructural findings to confirm a more isotropic material was successfully achieved.